Digital farming, invisible farmers - María del Pilar Ramírez Gröbli (Alternautas, 2022)
Digital technologies have been gradually penetrating agricultural production systems; specially, in the last two decades, generating both expectations and concerns because of the unknown technological scope and the speed of the transformations. While some sectors are enthusiastic on the potential of digital tools have to contribute efficiently in food production, to achieve agri-food sustainability and to mitigate climate change, others are concerned about the challenges digital technologic will produce on political, social and cultural fields. The embeddedness, conditions, and usage of digital technologies in the agriculture sector raise questions on how and who participates on Global Production Networks and shape governance structures and policies orientation underpinning them. In the current landscape, just some few Global Networks with different forms of economic and political power are dominating digitalisation worldwide. They have the control of technologies to implement digital agriculture at the global scale. Governmental institutions both at international and national level foster financial and market policies to invest and promote in digitalisation what has impacts on the shifting of food systems. This article examines the dynamics of power concentration wielded by the Global Networks that, through large transnational corporations, have managed to dominate different sectors of the food chain by implementing digital systems for agriculture.  It also presents an analysis of land concentration and big data and the possible implications for small producers and traditional food systems in Latin America. It suggests that while some digital services can contribute to improving and alleviating the challenges facing agricultural production, others could increase the concentration of power in a few hands by appropriating sensitive information from Big Data and adapting it to industrial food production and food value chains and posing fundamental challenges to governance structures.